Trends and Reinterventions in the Surgical Management of Stress Urinary Incontinence among Female Medicare Beneficiaries. Issue 5 (September 2016) - Chughtai, Bilal; Buck, Jessica; Anger, Jennifer; Asfaw, Tirsit; Mao, Jialin; Lee, Richard; Te, Alexis; Kaplan, Steven; Sedrakyan, Art
Abstract : Introduction: : We compare the use of bulking agents and slings for the treatment of stress urinary incontinence among female Medicare beneficiaries. Methods: : We analyzed data from a 5% national random sample of Medicare claims from 2000 to 2011. Female beneficiaries who underwent a sling or bulking agent procedure were identified based on CPT‐4 and ICD‐9 procedure codes. Statistical analysis for categorical data determined differences in the distribution of patient demographics and comorbidities. The 90‐day adverse events and reinterventions were compared between treatment groups. Time to event analysis was used to determine freedom from reintervention after therapy. Results: : We identified 21, 134 and 3, 475 patients treated with sling and bulking procedures, respectively. There was a 29.7% increase in the number of sling procedures and a 59.5% decrease in bulking procedures from 2001 to 2011. Patients treated with bulking agents had higher rates of diabetes, cardiovascular disease, heart failure and renal failure (p <0.01). The 90‐day adverse events after both procedures were rare, with the exception of urinary retention, which was increased in women treated with a sling but frequent in both groups (sling 11.3%, bulking agent 8.4%; p <0.01). A smaller proportion of patients who underwent sling surgery had reinterventions (repeat sling 7.4%, bulking agent 38.2%; p <0.01). Overall 53.2% of the patients treated with a sling and 76.3% treated with bulking agents who underwent subsequent procedures were treated with the same procedure at the first intervention. Conclusions: : Sling and bulking procedures are safe in terms of short‐term performance, although the rates of retention were high in both groups. Patients treated with reinterventions tend to repeat the same therapy instead of converting to another procedure.